2011
DOI: 10.1582/leukos.2011.07.03003
|View full text |Cite
|
Sign up to set email alerts
|

Visual Comfort Analysis of Innovative Interior and Exterior Shading Systems for Commercial Buildings using High Resolution Luminance Images

Abstract: The objective of this study was to explore how calibrated high dynamic range (HDR) images (luminance maps) acquired in real world daylit environments can be used to characterize, evaluate, and compare visual comfort conditions of innovative facade shading and light-redirecting systems. Detailed (1536 ϫ 1536 pixel) luminance maps were time-lapse acquired from two view positions in an unoccupied full scale testbed facility. These maps were analyzed using existing visual comfort metrics to quantify how innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…They argued that luminancebased metrics were more capable than illuminance-based metrics in predicting a user's visual preference. Luminance maps indicated that more detailed spatial analysis was needed when assessing the visual comfort performance of innovative facade systems (Konis et al 2011). One study (Chatzikonstantinou and Sariyildiz 2016) experimented with using machine learning techniques on data from simulation results of visual comfort analysis of office spaces.…”
Section: A Review Of the Criteria For Objective Assessment Of Visualmentioning
confidence: 99%
“…They argued that luminancebased metrics were more capable than illuminance-based metrics in predicting a user's visual preference. Luminance maps indicated that more detailed spatial analysis was needed when assessing the visual comfort performance of innovative facade systems (Konis et al 2011). One study (Chatzikonstantinou and Sariyildiz 2016) experimented with using machine learning techniques on data from simulation results of visual comfort analysis of office spaces.…”
Section: A Review Of the Criteria For Objective Assessment Of Visualmentioning
confidence: 99%
“…In (Konis et al 2011) One of the possible applications of the HDRI technique for analysis is represented in (Van et al 2010). Authors study preference of occupants in a daylit office environment and the acceptance of luminance patterns using the HDR imaging.…”
Section: Studies Of the Hdri Technique Capturing A Natural Scene And/mentioning
confidence: 99%
“…HDRI technique is already widely used in lighting research. There are studies on assessing HDRI"s accuracy for various lighting applications (Inanici 2006;Moeck et al 2006;Moeck 2007;Inanici 2010;Konis et al 2011;Cai et al 2011). The HDRI tool still has to be evaluated for accuracy and reliability in the lighting field to gain more statistical data and to expand HDRI"s abilities.…”
mentioning
confidence: 99%
“…Specifically, in visual comfort studies it can provide luminosity ranges within a field of view (FOV) that would not be normally possible with other types of photometric instruments (i.e., Luminance meters). To date, many post-occupancy studies in visual comfort research have adopted this approach to assess the subjective experiences of discomfort glare in buildings [4][5][6][7][8]. This is because a camera with fisheye lens can capture Low Dynamic Range (LDR) images to generate HDR images with a field of view similar to a human's field of view (FOV).…”
Section: Introductionmentioning
confidence: 99%